NILAI TAMBAH DAN STRATEGI PENGEMBANGAN DI AGROINDUSTRI TEPUNG TAPIOKA X DI KECAMATAN KALIREJO KABUPATEN LAMPUNG TENGAH - Maulita, Dwi; Sayekti, Wuryaningsih Dwi; Zakaria, Wan Abbas (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2020)
The purposes of this research are to analyze the added value of tapioca flour, identifying the internal and external environment, and formulate development strategies of tapioca flour agroindustry X in Kalirejo Sub- District. The research method is a case study and data used are primary and secondary data. The data are analyzed by using descriptive qualitative and quantitative analysis. The results showed that tapioca flour agroindustry X provided added value of IDR4,475.03/kg of tapioca flour (63.28 %) in grade A; IDR4,084.74/kg of tapioca flour (61.16 %) in grade B; and IDR2,897.05/kg of tapioca flour (52.67 %) in grade C. The internal environment which is the strength of tapioca flour agroindustry X is a quality tapioca flour product and the weakness is the unskilled agro-industry workforce. The external environment which is the opportunity for tapioca flour agroindustry X is technology and the threat is the high product competitiveness. Strategies of tapioca flour agroindustry X are as follows: (a) utilizing quality tapioca flour products to meet consumer demand, (b) utilizing the existence of modern technology by conducting training for workers, (c) increasing the availability of materials standards to meet technological capacity in production, (d) increasing cooperation with suppliers of raw materials to overcome the shortage of raw materials due to the large number of competitors in the same business, and (e) increasing business profits by maximizing the use of technology. Key words: added-value, development strategy, internal and external environment, tapioca flour.